IT Balanced Scorecard Implementation to Measure Information Technology Performance on Information Technology Division of PT. Samudera Indonesia Tbk. - Mastuki, Mastuki (ComTech: Computer, Mathematics and Engineering Applications, 2015)
The goals of this thesis were to measure the performance of information technology in the IT Division of PT. Samudera Indonesia Tbk. using IT Balanced Scorecard (IT BSC), in which from each of its perspective was breakdown into related variables used as a model of optimal measurement. The problems that will be discussed in this research consisted of finding the factors required to measure the performance of information technology in the company; determining the indicators in measuring the IT performance; understanding in how to create the optimal measurement model of IT performance and evaluating how the measurement model affected the IT performance. The compiled data through questionnaires will be analyzed using factor analysismethod through five steps: problem formulation, correlation matrix, determining the number of factors, factor rotation, and factor interpretation. The result of the research showed that there were four factors affected the ITperformance in PT. Samudera Indonesia Tbk. which consist of IT Competency, IT Services Ability, Business Continuity and IT Improvement. Thus, it can be concluded that those factors affected the IT performance and to obtain a good quality of IT performance, each indicator of the factors should be done to the fullest.